Safety of warfarin therapy during cataract surgery under topical anesthesia - Kara-Junior,Newton (2015)
ABSTRACT Purpose: To analyze the safety of warfarin therapy during cataract surgery under topical anesthesia. Methods: This was a prospective nonrandomized comparative study of 60 eyes of 60 patients treated with or without concurrent oral warfarin anticoagulant therapy, referred for cataract surgery under topical anesthesia. The sample included a treatment (n=30) and a control (n=30) group. Results: There were no records of intraoperative or postoperative intracameral bleeding complications in both the groups. At 1-month postoperative follow-up, 90.0% of patients presented spectacle-corrected visual acuity of at least 20/40. Conclusion: Cataract surgery by phacoemulsification with topical anesthesia can be successfully conducted without discontinuing warfarin.